Targeted inhibition of STAT/TET1 axis as a therapeutic strategy for acute myeloid leukemia - Xi Jiang (Nature Portfolio, 2017)
Ten-eleven translocation 1 (TET1) is a critical oncoprotein in AML. Here, the authors identify 2 compounds that target the binding of STAT3/5 specifically to the TET1 promoter, inhibiting its expression and AML cell viability.